Modern approaches to cardiovascular amyloidosis treatment - Svetlana N. Morozkina; Petr P. Snetkov; Roman O. Olekhnovich; Mayya V. Uspenskaya (Russian Open Medical Journal)
Cardiovascular (cardiac) amyloidosis (CA) is a clinical pathology, usually of a geneticallymediated nature, initiated by the precipitation process of the insoluble fibrous protein with β-pleated sheet secondary structure. Such anomalous changes lead to the formation of amyloid fibrils, which may give rise to various forms of amyloidosis. Amyloid formation can be found in various organs and systems, such as cardiovascular system, central and peripheral nervous systems, liver, urinary tract, etc. CA is a rare degenerative disease resulting in congestive cardiac failure and heart arrhythmia with subsequent untimely death. Unfortunately, up to date, the choice of medications for treating amyloidosis is very limited. In this paper, we review clinically used pharmaceutical drugs for CA treatment, along with some delivery systems for such compounds.